ANALYSIS OF THE APPLICATION OF HOSPITAL MANAGEMENT INFORMATION SYSTEM (SIMRS) IN ‎OUTPATIENT SERVICES AT DR. M.M. DUNDA LIMBOTO - Darman; Tri Liswinda Umar indi; Desi Novitasari (Jurnal Ilmiah dr. Aloei Saboe, 2024)
The implementation of Management Information System (SIM) for a hospital is very important in its application in the present era. This is supported by the increasing complexity of the problems that exist in the patient's medical data and other administrative data related to the implementation of hospital services received by the patient. This research was conducted at Dr. M.M. Dunda Limboto. the approach in the study is a qualitative approach and the type used is descriptive research that aims to analyze the application of Management Information System (SIMRS) in outpatient care at Dr. M.M. Dunda Limbotomelalui 6 aspek PIECES (performance, information, economy control, efficiency, dan service). Based on the results of research conducted it can be concluded that the application of Hospital Management Information System (SIMRS) in outpatient care at Dr. M.M. Dunda Limbotomelalui 6 aspek PIECES (performance, information, economy control, efficiency, dan servicesudahdilakukandengancukupbaik. Related obstacles that arise in the field when implementing the hospital Management Information System (SIMRS) occur due to error constraints from the system, network and some features in the SIMRS application such as outpatient registration forms or medical and laboratory record forms).